2022
DOI: 10.3390/agriculture12070944
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Urea–Chitosan Nanohybrid for Minimizing Synthetic Urea Application and Maximizing Oryza sativa L. Productivity and N Uptake

Abstract: In paddy fields, overuse of nitrogen fertilizer to maximize yields can lead to excessive economic loss and degradation of the environment. Therefore, studying the effects of urea–chitosan nanohybrid as a slow released source of nitrogen fertilizer on rice cultivation was the aim of our study. The effects of fertilization applications, namely: CU: control treatment; U1: application of a full recommended dose of classical urea (165 kg N ha−1); U2: adding recommended dose of classical urea by 80% + exogenous urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…Applying CaP-U NPs to Triticum durum Desf., significantly increased the fresh and dry weight of the shoot ( Ramírez-Rodríguez et al., 2020b ). Rice plants fertilized with exogenous urea–chitosan nanohybrid (i.e., 500 mg/L) + 60% classical urea, significantly enhanced the growth and yield-related traits ( Elshayb et al., 2022 ). In Sorghum bicolor (L.) Moench, application of the calcium nitrate-gelatin (CNG) coated urea showed maximum dry matter accumulation, high average plant chlorophyll content and apparent nitrogen recovery (ANR) of 71.14% in shoot and 4.5% in roots, respectively ( Khan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Applying CaP-U NPs to Triticum durum Desf., significantly increased the fresh and dry weight of the shoot ( Ramírez-Rodríguez et al., 2020b ). Rice plants fertilized with exogenous urea–chitosan nanohybrid (i.e., 500 mg/L) + 60% classical urea, significantly enhanced the growth and yield-related traits ( Elshayb et al., 2022 ). In Sorghum bicolor (L.) Moench, application of the calcium nitrate-gelatin (CNG) coated urea showed maximum dry matter accumulation, high average plant chlorophyll content and apparent nitrogen recovery (ANR) of 71.14% in shoot and 4.5% in roots, respectively ( Khan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can increase growth, yields and quality of crops, and also plants tolerance or resistance to biotic and abiotic stresses (Tarafdar et al, 2013). Use of engineered smart nanotools in high-tech agricultural system could be brilliant approach to make revolutions in agricultural practices to yields and quality, and thus decrease and/or eradicate the negative impact of current agriculture on climate (Sekhon, 2014;Liu and Lal, 2015;Elshayb et al, 2022a;Al-Selwey et al, 2023). Recent studies showed that application chitosan nanoparticles in tomato and maize, silver nanoparticles s in wheat and multi-walled carbon nanotubes in broccoli significantly alleviated negative effects of salinity stress (Bruna et al, 2016;Martinez-Ballesta et al, 2016;Mohamed et al, 2017;HernandezHernandez et al, 2018;Abou-Zeid and Ismail, 2018).…”
Section: Use Of Nanotechnologymentioning
confidence: 99%
“…The incursion of nanotechnology in agriculture is relatively recent, where the production of nanocomposites containing fertilizers, pesticides, and microorganisms is one of the most important applications ( Usman et al., 2020 ; Elshayb et al., 2022 ). For instance, nano-biosensors are playing an important role in revolutionizing farming through the development of diagnostic tools and techniques for identifying heavy metal (HM) ions, pollutants, microbial load, and pathogens, along with fast environmental monitoring.…”
Section: Agricultural Potential and Plant Effect Of Npsmentioning
confidence: 99%